Estudo preliminar do potencial de alguns asteroides - Moura, Tamires dos Santos de [UNESP] (2014)
A survey we conducted, and bring expressed in this text is a preliminary study on the shape of asteroids and allowed us to understand a little more the dynamics around these bodies, in order that the images we have of asteroids are the most irregular possible. In this work, the asteroid is modeled by the method of the polyhedron, which provides a very good accuracy of the irregular shape of the body. Through study of models for non-spherical gravitational potential bodies, implementation of computational algorithms and numerical simulations a preliminary analysis was performed in relation to the shape of asteroids 4179 Toutatis, 6489 Golevka, 2063 Bacchus, 1620 Geographos and 1998 ML14, as well as regions of stability instability, we compute the coefficients of the gravitational potential. The work not only enables expansion for the case of asteroids, but also for other non-spherical bodies, contributing to the development of targeted studies the origin and evolution of the solar system, and perhaps the origin of the earth, and new technologies for modeling and mapping of non-spherical bodies. The main results were obtained by analyzing the graphics format and planning of asteroids, which confirmed how these bodies are irregular and show how distribution of non-homogeneous mass. Observe the behavior of the curves of zero velocity and equipotential curves as well as their respective surfaces. Also, compute some values of the gravitational potential and the spherical harmonic coefficients of each object. Furthermore, we find possible equilibrium points of asteroids except 4179 Toutatis, and analyze its stability